Cell-free prion protein conversion assays in screening for anti-prion drug candidates. (February 2019) - do Carmo Ferreira, Natália; Caughey, Byron
Highlights: Inhibiting PrP C to PrP res conversion is a key treatment strategy for prion diseases. Cell free prion-seeded PrP conversion assays help identify new anti-prion drugs. Samples from infected patients provide diverse clinically relevant prion seeds. Abstract : The search for medications to treat prion diseases has lasted more than 30 years but no clinically validated treatments for prion diseases of humans or livestock have been realized. A primary strategy has been to identify molecules that can inhibit the formation of pathological forms of prion protein, for example, protease-resistant forms called PrP res . Such inhibitors can prolong the lives of experimental animals inoculated peripherally with prions, but the practical therapeutic efficacy of known inhibitors against ongoing brain infections has so far been limited by toxicity, insufficient bioavailability to the CNS, and/or strain specificities. Thus, the search continues for clinically applicable inhibitors of PrP res accumulation. Here we highlight key cell-free assays that are useful for the initial screening and mechanistic characterization of such compounds and are relatively high throughput, rapid, and cost-effective. These include cell-free conversions, protein misfolding cyclic amplification (PMCA), real time quaking-induced conversion (RT-QuIC), and fluorescence correlation-based competitive binding assays.